Heat transfer analysis of different cooling medium on a condenser / Muhammad Faris Saiful Anuar - Saiful Anuar, Muhammad Faris (2022)
One of the cooling devices that can induce condensation to high-pressure refrigerants by ventilating the heat of the high-temperature refrigerant meanwhile at the same time maintain its pressure is the condenser. The cooling medium that being applied in it is vital because it will result in the effectiveness of the condenser. The most functioning cooling mediums to be used is coolant fluid. This research purpose is to analysis the performance of the condenser and to improve it by improving the heat transfer features and cooling rates of the device including coolants, the same coolant but with two different concentrations, and the mass flow rates. The working fluids that being used are water as Coolant A, and Coolant X with two different concentrations such as Coolant B with 13% of concentration and Coolant C with 15% of concentration and the mass flow rate is use at the range from 0.5 l/s until 4.0 l/s. The temperature of every coolant at the inlet initially will be constant at 26°C and when running the experiment each coolant runs through the piping system, passing through the condenser, which dissipates any unnecessary heat before exiting the pipe. Next, before and after passing through the condenser both temperatures of the coolant were measured using the thermocouple that is provided. For this study, the result that can be expected from this experiment is that Coolant C with 15% of concentration may be the best coolant for the condenser because of its heat transfer analysis and follow up with the Coolant B with 13% of concentration and the last coolant from this study is the Coolant A which is water.